2014
DOI: 10.1111/add.12623
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of e-cigarettes when used to aid smoking cessation: a cross-sectional population study

Abstract: Background and AimsElectronic cigarettes (e-cigarettes) are rapidly increasing in popularity. Two randomized controlled trials have suggested that e-cigarettes can aid smoking cessation, but there are many factors that could influence their real-world effectiveness. This study aimed to assess, using an established methodology, the effectiveness of e-cigarettes when used to aid smoking cessation compared with nicotine replacement therapy (NRT) bought over-the-counter and with unaided quitting in the general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
335
3
21

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(375 citation statements)
references
References 54 publications
16
335
3
21
Order By: Relevance
“…[15][16][17][18][19][20][21] Despite these concerns, a recent cross-sectional, retrospective study found that e-cigarette users in the general population were more likely than NRT users to have quit cigarette smoking. 22 In comparison to cigarettes, available evidence suggests that e-cigarettes are a safer nicotine delivery system. For example, levels of toxicants in e-cigarette vapor have been reported to be 9-450 times lower than in cigarette smoke 12 and particle emissions have been reported to be 5-10 times lower.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Despite these concerns, a recent cross-sectional, retrospective study found that e-cigarette users in the general population were more likely than NRT users to have quit cigarette smoking. 22 In comparison to cigarettes, available evidence suggests that e-cigarettes are a safer nicotine delivery system. For example, levels of toxicants in e-cigarette vapor have been reported to be 9-450 times lower than in cigarette smoke 12 and particle emissions have been reported to be 5-10 times lower.…”
mentioning
confidence: 99%
“…8 In 2014, a cross sectional study was conducted in England following 5,863 smokers who attempted to quit in the last 12 months without professional support. 9 The authors reported that those who used ENDS fared better compared to those who used over the counter NRT (adjusted OR=1.63, 95% CI=1. 17-2.27) An ENDS product is yet to be approved as a medicinal product for smoking cessation by any governmental agency, although the UK's Medicines and Healthcare Products Regulatory Agency is in the process of reviewing some of these products.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…Tiriant elektroninių cigarečių poveikį metant rūkyti gauti prieštaringi rezultatai (13,(63)(64)(65)(66)(67)(68)(69). Kai kuriais tyrimais nustatyta, kad el.…”
Section: Elektroninių Cigarečių Vaidmuo Metant Rūkytiunclassified
“…cigaretes vartoję tiriamieji, kurie bandė mesti rūkyti be profesionalios specialisto pagalbos, dažniau nurodė užsitę-susius nikotino abstinencijos simptomus, palyginti su vartojusiais pakaitinės nikotino terapijos priemones ar nenaudojusiais jokių priemonių (69).…”
Section: Elektroninių Cigarečių Vaidmuo Metant Rūkytiunclassified